Implementation of biometric system against immigrant workers in Malaysia: an appraisal for national security / Hendun Abd Rahman Shah - Abd Rahman Shah, Hendun (2014)
Despite foreseen problem associated with the lenient policy of unrelentingly engaging foreign workers in Malaysia, the government is not ready to stop or prohibited the dependence on this immigrant totally. The initiative of implementing the biometric system is timely in order to ensure the national security is not threatened by the influx of illegal immigrant workers to Malaysia. The paper begins with the background study of foreign immigrant in Malaysia and several biometric technologies that already been implemented. It then studies the history of biometric system before deliberating the issues surrounding foreign workers and illegal immigrant. Then, the central issue on the important of having biometric system for the purpose of tightening national security is examined. Finally the paper concludes with suggestion of weighing the national interest and immigrant’s rights and privacy, while upholding integrity of the officers responsible in implementing the system.